Phocaeicola dorei ameliorates progression of steatotic liver disease by regulating bile acid, lipid, inflammation and proliferation - Jieun Choi; Ye Rin Choi; Min Kyo Jeong; Hyun Ho Song; Jeong Seok Yu; Seol Hui Song; Jeong Ha Park; Min Ju Kim; Hyunjoon Park; Young Lim Ham; Sang Hak Han; Dong Joon Kim; et al. (Gut Microbes, 2025)
Gut microbiota and their metabolites are known to influence the pathogenesis and progression of metabolic dysfunction-associated steatotic liver disease (MASLD). In this study, we investigated the potential beneficial effects of Phocaeicola dorei in modulating MASLD progression, beginning with clinical observations and followed by mechanistic validation in animal models. Human data (49 healthy controls and 129 MASLD patients) were collected to investigate gut microbial biomarkers. The relative abundance of P. dorei was found to significantly vary with MASLD severity in human. Western diet-induced MASLD mice supplemented with P. dorei (12 weeks, 109 CFU/g twice/week) or 100 μl of P. dorei cell-free supernatant (CFS, 5 times/week) were utilized. STAMTM mice (10 weeks, 108 CFU/g four times/week) and RAW 264.7 cells were used for the validation. MASLD severity was determined based on liver/body weight, pathology, and biochemistry markers. Cecum feces were collected for 16S rRNA gene sequencing and metabolite profiles. In the animal model, P. dorei oral administration and its CFS alleviated lipid accumulation by increasing β-oxidation gene expression and inhibited inflammatory response from fatty liver to hepatitis progression. In the STAMTM model, P. dorei decreased nuclear atypia and cell proliferation. Additionally, P. dorei CFS inhibited TNF-α and CXCL10 in activated macrophages, and this result was consistent with the results of animal models. P. dorei and its metabolites ameliorate MASLD progression by modulating bile acid, lipid accumulation, inflammation, and proliferation. P. dorei could be a promising candidate for novel microbiota-based therapeutic strategies against MASLD.